Do Takeover Defense Indices Measure Takeover Deterrence? - Karpoff, Jonathan M.; Schonlau, Robert J.; Wehrly, Eric W. (Review of Financial Studies, 2017)
Many researchers use the G-index or E-index to measure firms’ takeover defenses. Others argue that these indices are not related to firms’ takeover likelihoods. We find that, unlike their raw values, the instrumented versions of these indices are significantly and negatively related to acquisition likelihood. The difference between the raw and instrumented results indicates that the G-index and E-index include an endogenous component and highlights the importance of accounting for endogeneity in tests that use takeover indices to measure takeover deterrence. We provide data on new instruments that researchers can use to address these issues.Received April 13, 2016; editorial decision October 14, 2016 by Editor David Dennis.